Dynamics of the relationship between stock markets and exchange rates during quantitative easing and tightening - Farzaneh Ahmadian-Yazdi; Amin Sokhanvar; Soheil Roudari; Aviral Kumar Tiwari (Financial Innovation)
Abstract This study utilizes two complementary models, the Time-Varying Parameter Vector Autoregressive Diebold–Yilmaz (TVP-VAR-DY) and the Time-Varying Parameter Vector Autoregressive Baruník–Křehlík (TVP-VAR-BK), to investigate the dynamic volatility transmission between exchange rates and stock returns in major commodity-exporting and -importing countries. The analysis focuses on periods of quantitative easing (QE) and quantitative tightening (QT) from March 15, 2020 to December 30, 2022. The countries examined are Canada and Australia (major commodity exporters) and the UK and Germany (major commodity importers). An essential contribution of this paper is new empirical insights into the dynamics of stock market returns and the transmission of volatility between these markets and exchange rates during the QE and QT periods. The results reveal that causality primarily flows from stock markets to exchange rates, especially during the QT period across all investment horizons. The Toronto Stock Exchange (TSX) emerges as the principal net driver among the markets under study. Furthermore, the Canadian exchange rate (USDCAD) and the Australian Stock Exchange (ASX) are the most significantly affected indices within the network across various investment horizons (excluding the long-term). These findings underscore the importance for investors and policymakers to consider the interplay between exchange rates and stock market returns, particularly in the context of the QE and QT periods, as well as other economic, political, and health-related events. Our findings are relevant to various stakeholders, including governments, traders, portfolio managers, and multinationals.